Strategi Manajemen Keuangan Rumah Tangga: Langkah Menuju Kesejahteraan Ekonomi Keluarga - Hani Hasanah; Budiastuti Fatkar; Dwi Sri Dani Afriza; Teuku Fajar Shadiq (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This Community Service activity aims to ensure that every woman is able to have a management strategy in managing household finances so that economic prosperity can be achieved in the family. Participants in this activity are given an understanding of the management strategies applied in managing household finances which will result in output from the participants, namely that each participant knows the level of financial needs, is able to make financial plans well in accordance with the flow of the management process, has an effective financial management strategy and practice in preparing routine financial budgets. It is important to carry out this activity because of economic instability and the increasing cost of living nowadays. It is very necessary to educate the public, especially women, in financial literacy to manage household finances well and optimally. This is an open access article under the CC–BY-SA license